The EVIDENCE FROM THE HYBRID VEHICLE MARKET ON CLIMATE CHANGE AND SUSTAINABLE PRODUCT CONSUMPTION - Kanwal Jit Singh , Kewal Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Firms must better understand the motivations behind the purchasing of these items as sustainable consumption becomes more essential. In the context of the U.S. hybrid car market, this article investigates the influence of mass media. Monthly sales data shows that the general coverage of climate change or global warming by major media outlets has a beneficial influence on the sales of hybrid automobiles. Climate change deniers in the media are largely to blame for this effect. While climate change denial or neutral reporting has minimal influence, the opposite is true with media coverage. According to the authors' findings, media coverage of environmentally friendly products has a significant impact on customer purchases. Research on the causal influence of media on consumer decisions, particularly those that are critical to society, is needed, as are their implications for theory and practise.